(untitled) (American Journal of Business Management, Economics and Banking, 2026)
The downscaling activities of commercial banks and innovative financial services offer by other financial institutions continuously exposed the microfinance institutions to stiff competition necessitating the quest of new strategies of growth. Alliances have become imperative in enterprise growth thus the formation of Share-supply alliances in the microfinance sector. This study aims to examine the influence of shared-supply alliances on the sustainability of MFIs in Cameroon. The objectives are to examine how shared-supply alliances in the Production of Financial Services (PFIS) and shared-supply alliances in the Production of Non-Financial Services (PNFIS) affect the sustainability of MFIs in Cameroon.